The Effects of the Preparation Factors on the Properties of CO2 Capture Sorbent Derived from Local Waste Eggshell - Chuanchob, Janjeera; Piumsomboon, Pornpote; Chalermsinsuwan, Benjapon; Chanchairoek, Saowaluck (Applied Environmental Research, 2023)
In this study, the CaO adsorbent was prepared by using local waste eggshell as a raw material. The influence of preparation parameters including calcination temperature, calcination time and particle size of eggshell powder on the adsorption surface area were investigated. By means of statistically experiment design, the interesting parameters were investigated by a full 23 factorial design. The prepared sorbent material was characterized by X–ray diffraction (XRD), Scanning electron microscopy (SEM) and the Brunauer–Emmet–Teller (BET). The results showed the particle size of eggshell powder greatly affected the BET surface area. By applying the prepared condition of 149 μm in particle size, 6 h of calcination time and 1,000oC calcination temperature, the obtained CaO adsorbent yielded the highest in BET surface area of 5.023 m2 g-1. The CO2 performance test in the fluidized bed reactor with 12% V/V CO2 in N2 balance also revealed that the local waste eggshell can be used as CO2 adsorbent. The CO2 carrying capacity of the highest BET surface area sorbent was 0.011 g CO2 g-1 sorbent at 700°C carbonation temperature.